THE USE OF NUMBERED HEAD TOGETHER (NHT) TECHNIQUE WITH DESCRIPTIVE TEXT TO IMPROVE THE TENTH GRADE STUDENTS READING COMPREHENSION OF SMA MUHAMMADIYAH 1 PALEMBANG - Tri Fuspa Wilanda; Jaya Nur Iman (Global Expert: Jurnal Bahasa dan Sastra, 2018)
The aim of this research attempted to determine whether using NHT technique significantly improved the students’ reading comprehension and significantly made a difference on the students’ reading comprehension who were taught by using NHT and those who were not A Quasi Experimental design was used as the research method. The sampling technique used in this research was purposive sampling. Pretest and posttest, in the form of Reading comprehension test, were used to collect the data of students’ reading comprehension. Paired samples and independent samples t-tests were employed to calculate the students’ reading comprehension achievement. The research findings showed that there was a significant improvement on the students’ reading comprehension who were taught by using NHT technique and there was a significant difference between the students reading comprehension who were taught by using NHT and those who were not.Key words : Numbered Heads Together, reading comprehension, descriptive text